Modified PET (Polyethylene Terephthalate) material with good blood compatibility and antibacterial ability as well as preparation method and application of modified PET material

By grafting halogen-containing bisaziridine compounds, end aminopolyamide dendrimers and heparin oxide on the surface of PET materials, the problem of insufficient thrombus aggregation and antibacterial ability of PET materials in in vivo implantation equipment is solved, and the problem of insufficient thrombus aggregation and antibacterial ability of PET materials in vivo implantation equipment is achieved. Good hemocompatibility and antibacterial effects.

CN119431862APending Publication Date: 2025-02-14BEIJING UNIV OF CHEM TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411277794.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing PET materials are prone to gathering thrombus in in vivo implantation equipment and are difficult to have good blood compatibility and antibacterial ability at the same time, resulting in safety hazards.

Method used

Modified PET is formed by grafting the halogen-containing bisaziridine compounds and end aminopolyamide dendrimers with antibacterial ability on the surface of the PET material and grafting with heparin oxide under optional conditions to form a modified PET material by grafting it in turn with heparin. Material.

Benefits of technology

It has achieved the improvement of antibacterial ability and hemocompatibility on the surface of PET materials, and can kill more than 50% of Staphylococcus aureus and E. coli, while reducing the platelet adhesion density and hemolysis rate. It is suitable for the manufacturing of in vivo implantation equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431862A_ABST
    Figure CN119431862A_ABST
Patent Text Reader

Abstract

The invention discloses a modified PET (Polyethylene Terephthalate) material with good blood compatibility and antibacterial ability as well as a preparation method and application thereof. The modified PET material disclosed by the invention is obtained by sequentially grafting a halogen-containing bis-aziridine compound, an amino-terminated polyamidoamine dendritic polymer with antibacterial ability and oxidized heparin on the surface of a PET material. The invention provides two modified PET materials, the first modified PET material has good antibacterial ability and can kill more than 50% of staphylococcus aureus and Escherichia coli, and the second modified PET material has good blood compatibility and antibacterial ability and can kill more than 50% of staphylococcus aureus and Escherichia coli while killing more than 50% of staphylococcus aureus and Escherichia coli. The adhesion density of platelets on the surface of the film is reduced to 80% or below of that of an untreated PET film, the hemolysis rate is smaller than 2%, rat epidermal tissue does not generate obvious reaction on the film, and the film has good blood compatibility and antibacterial ability, can be used for manufacturing biological devices such as in-vivo implantation equipment and has very good application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PET material modification, and more specifically, to a modified PET material, a preparation method thereof, and an application thereof, and further to a modified PET material having both good blood compatibility and antibacterial ability, a preparation method thereof, and an application thereof. Background Art

[0002] Due to the low density and good biocompatibility of polymer materials, they are widely used in the manufacture of implantable devices in the body. However, polymer materials are prone to blood clots accumulating on their surfaces and becoming ineffective, making them difficult to put into practical applications. One solution is to add anticoagulants, such as heparin, to the polymer to prevent blood clots from forming on the surface. However, the addition of anticoagulants can significantly affect the mechanical and optical properties of polymer materials, limiting their use. In addition, the activity of anticoagulants is inevitably limited. In order to achieve the specified antithrombotic effect, a large amount of anticoagulant needs to be added, which may cause hemolytic interference or thrombocytopenia, endangering human health. Therefore, a solution that uses less anticoagulants is urgently needed.

[0003] Grafting anticoagulant derivatives onto polymer surfaces is an effective approach to addressing these issues: First, grafting anticoagulant derivatives onto the surface does not affect the polymer itself and has minimal impact on the mechanical and optical properties of the polymer. Second, because the activity of anticoagulants is related to their anticoagulant sequence, the use of derivatives does not significantly affect their anticoagulant activity. Third, the amount of anticoagulant derivatives grafted onto the surface is generally small, does not cause induced symptoms such as thrombocytopenia, and has good biocompatibility. However, polymer materials used for implantable devices, such as polyethylene terephthalate (PET), do not have side groups or side chains that can be used for surface grafting. Therefore, how to graft anticoagulant derivatives onto the surface of medical polymers such as PET is a bottleneck problem in current medical polymer surface modification methods.

[0004] Furthermore, during implantation of medical devices, pathogens such as bacteria may accumulate on polymer surfaces, leading to wound infections and potentially life-threatening conditions. Currently, the primary approach to addressing this issue is the introduction of antibiotics. However, antibiotics also kill red blood cells (RBCs) in the blood, causing hemolysis. Therefore, imparting antimicrobial properties to polymer surfaces while maintaining good blood compatibility is a key challenge in surface modification of medical polymer materials.

[0005] Therefore, how to obtain a modified PET material with good antibacterial and / or blood compatibility is a technical problem that needs to be solved at present. Summary of the Invention

[0006] To address the problems encountered in the prior art, the present invention proposes a modified PET material with both excellent blood compatibility and antibacterial properties, as well as its preparation method and application. The present invention provides two modified PET materials. The first modified PET material exhibits excellent antibacterial properties, capable of killing over 50% of Staphylococcus aureus and Escherichia coli. The second modified PET material exhibits both excellent blood compatibility and antibacterial properties. While killing over 50% of Staphylococcus aureus and Escherichia coli, it also reduces the platelet adhesion density on the film surface to less than 80% of that of untreated PET film, resulting in a hemolysis rate of less than 2%. The film also exhibits no significant reaction in rat epidermal tissue. These materials exhibit both excellent blood compatibility and antibacterial properties, making them suitable for the manufacture of biological devices such as implantable devices, and possess excellent application value.

[0007] One of the objects of the present invention is to provide a modified PET material, which is obtained by grafting a halogen-containing diaziridine compound and an amino-terminated polyamidoamine dendrimer with antibacterial ability on the surface of a PET material in sequence, and then optionally grafting oxidized heparin.

[0008] In the modified PET material of the present invention, preferably,

[0009] The halogen-containing bisaziridine compound is a compound that can generate carbene radicals under ultraviolet light; preferably, the halogen-containing bisaziridine compound is selected from 4-[3-(trifluoromethyl)-3H-bisaziridine-3-yl]benzyl bromide.

[0010] In the modified PET material of the present invention, preferably,

[0011] The amino-terminated polyamidoamine dendrimer is at least one of a fifth-generation ethylenediamine core polyamidoamine dendrimer, a disulfide core polyamidoamine dendrimer, or a seventh-generation polyamidoamine dendrimer.

[0012] In the modified PET material of the present invention, preferably,

[0013] The oxidized heparin is a heparin derivative having an aldehyde group.

[0014] The present invention utilizes the characteristic of diazirine compounds that generate carbene free radicals under 365nm ultraviolet light. The diazirine compound (Br-Dia) is uniformly coated on the surface of polyethylene terephthalate (PET) film. Side chains useful for modification are then grafted via the carbene C-H bond insertion principle. An amino-terminated polyamidoamine dendrimer with strong antibacterial properties is then grafted onto the film. Finally, heparin is used as an anticoagulant, and an oxidized heparin derivative (i.e., oxidized heparin) with an aldehyde group is grafted onto the amino-terminated polyamidoamine dendrimer via a Schiff base reaction. Through the light-induced grafting of the diazirine compound, side groups useful for further modification are introduced onto the PET surface, addressing the current bottleneck of grafting onto medical polymers such as PET. Grafting the amino-terminated polyamidoamine dendrimer onto the PET surface improves the antibacterial properties of the PET film surface. By grafting the amino-terminated polyamidoamine dendrimer and the oxidized heparin derivative onto the PET surface, the key issues of poor blood compatibility and poor antibacterial properties of the PET film surface can be simultaneously addressed.

[0015] A second object of the present invention is to provide a method for preparing a modified PET material, comprising the following steps:

[0016] Step (1) grafting the PET material with a halogen-containing diaziridine compound to obtain an intermediate Dia-g-PET;

[0017] Step (2) grafting the intermediate Dia-g-PET with an amino-terminated polyamidoamine dendrimer having antibacterial ability to obtain a modified PET material PAMAM-g-PET;

[0018] Optionally, in step (3), the PAMAM-g-PET is subjected to a grafting reaction with oxidized heparin to obtain a modified PET material Hep-g-PET;

[0019] The modified PET material according to one of the objectives of the present invention is preferably prepared by the method.

[0020] In the above step (1) of the present invention, a side chain that can be used for modification is grafted and introduced through the C-H bond insertion principle of a carbene radical; wherein the carbene radical is generated by a diazirine compound under ultraviolet light, wherein there is no special requirement for the ultraviolet light, and it only needs to be able to achieve the above grafting reaction.

[0021] The diaziridine compound of the present invention is 4-[3-(trifluoromethyl)-3H-diaziridine-3-yl]benzyl bromide (denoted as Dia-Br or Br-Dia), and has the following structure:

[0022]

[0023] In the preparation method of the modified PET material of the present invention, preferably,

[0024] Step (1), washing the PET material, drying it, and then subjecting it to a grafting reaction with a halogen-containing diazirine compound under ultraviolet light;

[0025] Preferably,

[0026] The PET material is a PET film, and the halogen-containing diaziridine compound is evenly coated on the surface of the PET film and then subjected to a grafting reaction under ultraviolet light;

[0027] The ratio of the PET material to the halogen-containing diazirine compound is 1 cm 2 : 1.5~2.5μL; preferably 1cm 2 : 2.0~2.5μL;

[0028] During the grafting reaction, the wavelength of the ultraviolet light is 355 to 380 nm, preferably 365 to 370 nm;

[0029] The intensity of ultraviolet light is 0.4-0.6 mW / cm 2 ; preferably 0.4 to 0.5 mW / cm 2 ;

[0030] The UV light irradiation time is 4 to 6 minutes, preferably 5 to 6 minutes.

[0031] In the preparation method of the modified PET material of the present invention, preferably,

[0032] Step (2), immersing the intermediate Dia-g-PET in a solution containing the amino-terminated polyamidoamine dendrimer having antibacterial ability to carry out a grafting reaction,

[0033] Preferably,

[0034] The concentration of the solution of the amino-terminated polyamidoamine dendrimer having antibacterial ability is 0.8 to 1.1 wt %; preferably 0.9 to 1.0 wt %; and / or,

[0035] The grafting reaction is carried out in a closed environment. Further preferably, the grafting reaction temperature is 20 to 30° C.; preferably 23 to 25° C.; and / or,

[0036] The grafting reaction time is 8 to 12 hours, preferably 10 to 12 hours.

[0037] In the above step (2) of the present invention, the amino-terminated polyamidoamine dendrimer having antibacterial ability needs to satisfy the requirements of having antibacterial ability and having an amino-terminated structure. Preferably, the amino-terminated polyamidoamine dendrimer is at least one of a fifth-generation ethylenediamine core polyamidoamine dendrimer, a disulfide core polyamidoamine dendrimer, or a seventh-generation polyamidoamine dendrimer; wherein the disulfide core polyamidoamine dendrimer is an existing substance (refer to the report in New Advances in General Biomedical Applications of PAMAM Dendrimers Molecules 2018, 23, 2849; doi: 10.3390 / molecules23112849), and is also a polyamidoamine dendrimer having an amino-terminated structure, except that its core contains disulfide.

[0038] In the above step (2) of the present invention, taking the fifth generation ethylenediamine core polyamidoamine dendrimer (PAMAM) as an example, the dendrimer is grafted onto the PET surface (i.e., the intermediate Dia-g-PET surface) grafted with the diazirine compound prepared in the above step (1) through a substitution reaction between bromine atoms and amino groups. The reaction process is as follows:

[0039]

[0040] The dendrimer in question is a fifth-generation polyamidoamine dendrimer (PAMAM) with an ethylenediamine core. Because PAMAM's outer layer is rich in positively charged amino groups, it exhibits significant antimicrobial activity against common pathogens, such as Staphylococcus aureus and Escherichia coli, and can be used to functionalize the surface of PET films with antimicrobial properties. Furthermore, due to its topological structure, the outer amino groups are more reactive than those of linear molecules, favoring reactions with other groups, thereby achieving refunctionalization of the PET film surface.

[0041] In the preparation method of the modified PET material of the present invention, preferably,

[0042] Step (3), washing the PAMAM-g-PET, drying it, and immersing it in a solution containing oxidized heparin to carry out a grafting reaction to obtain a modified PET material Hep-g-PET;

[0043] Preferably,

[0044] The solution containing oxidized heparin is a solution prepared by oxidized heparin and PBS buffer; and / or,

[0045] The temperature of the grafting reaction is 20-30°C; preferably 23-25°C; and / or,

[0046] The grafting reaction time is 8 to 16 hours, preferably 12 to 16 hours;

[0047] Further preferably, the concentration of oxidized heparin in the solution containing oxidized heparin is 0.8 to 1.1 wt %; preferably 1.0 to 1.1 wt %; and / or,

[0048] The molar concentration of PBS in the solution containing oxidized heparin is 1.0-1.2 mol / L.

[0049] In the preparation method of the modified PET material of the present invention, preferably,

[0050] Step (3),

[0051] The oxidized heparin is a heparin derivative having an aldehyde group;

[0052] Preferably, the oxidized heparin is a heparin derivative having an aldehyde group obtained by oxidation with nitrous acid;

[0053] More preferably, the nitrous acid solution is reacted with the heparin sodium solution, neutralized with alkali, dialyzed, and freeze-dried to obtain oxidized heparin;

[0054] More preferably,

[0055] The concentration of the nitrous acid solution is 5.4 to 5.6 mol / L; and / or,

[0056] The concentration of the heparin sodium solution is 0.020-0.025 g / mL; and / or,

[0057] The volume ratio of the nitrous acid solution to the heparin sodium solution is 100:20-30; and / or,

[0058] The reaction time is 10 to 45 minutes; and / or,

[0059] The reaction temperature is 23-25°C; and / or,

[0060] The alkali used for the alkali neutralization is a sodium hydroxide aqueous solution, and the pH value is neutralized to 8.2-8.8.

[0061] In the above step (3) of the present invention, the oxidized heparin (anticoagulant derivative) used is heparin oxidized by nitrous acid, and the reaction formula is as follows:

[0062]

[0063] In formula (II), repeated -R are the same or different and are independently -H, -SO3 - Or CH3CO-. Among them, -H undergoes oxidation and cleavage at pH < 4, -SO3- Oxidative cleavage occurs when the pH is less than 1.5. In order to control the molecular weight of the heparin oxidized derivative and ensure its anticoagulant activity, it is preferably oxidized by an oxidant at pH = 1.5 to 4, such as nitrous acid.

[0064] The nitrous acid of the present invention is obtained by direct reaction of dilute sulfuric acid and sodium nitrite.

[0065] The nitrite-oxidized heparin of the present invention has an aldehyde group, which is grafted onto the terminal amino group of the dendrimer of the present invention through a Schiff base reaction. The principle of the Schiff base reaction is as follows:

[0066]

[0067] Most preferably, the preparation method of the modified PET material of the present invention is:

[0068] The diazirine compound is grafted onto the surface of the PET film. The specific preparation method is as follows: the surface of the PET film is ultrasonically cleaned with deionized water and methanol for 10 minutes in sequence, with the ultrasonic cleaning frequency being 80kHz. The PET film is then dried at 37°C for 8 hours. 2 μL of the diazirine compound is dropped onto a 1 cm 2 Use a PET brush to evenly and completely coat the center of the cleaned PET film surface. Then place it in a UV light box for reaction at an intensity of 0.5mW / cm 2 , illumination time 5 minutes.

[0069] The PET film grafted with the diazirine compound was immersed in the PAMAM solution and allowed to react in a closed environment at 25°C for 12 hours. After the reaction, the film was removed and ultrasonically cleaned in methanol for 10 minutes at 80 kHz. The film was then dried under vacuum to obtain a PET film grafted with dendrimer molecules.

[0070] The dendrimer molecule grafted PET film is stored in a dry environment at -4°C.

[0071] The method for synthesizing nitrous acid oxidized heparin described in the present invention is as follows: 0.5 mol / L dilute sulfuric acid and 5.5 mol / L sodium nitrite solution are mixed in a volume ratio of 28.5:71.5 to prepare 100 parts by volume of nitrous acid. The nitrous acid is prepared and used immediately. Deionized water is used to prepare 25 parts by volume of a 0.025 g / mL heparin sodium aqueous solution, and the nitrous acid is poured into the heparin sodium solution to start the reaction. The reaction time in the present invention is 10 to 45 minutes. After the reaction, 1 mol / L sodium hydroxide aqueous solution is gradually added for neutralization, and the solution is added dropwise until the pH value reaches 8.5. The neutralized solution is placed in an 8000Da dialysis bag and dialyzed with deionized water, with the water replaced at least every 3 hours and the deionized water replaced no less than 4 times. After dialysis, it is placed in a -80°C refrigerator and frozen for 12 hours. After freeze-drying with a freeze dryer, the nitrous acid oxidized heparin described in the present invention is obtained. The M of the oxidized heparin of the present invention w The molecular weight of the nitrite-oxidized heparin is determined by gel permeation chromatography (GPC).

[0072] The nitrite-oxidized heparin of the present invention is stored in a dry environment at 4°C.

[0073] During the synthesis of heparin oxidized by nitrite, the pH value can be measured using alkaline pH test paper or a pH meter.

[0074] A solution of the heparin nitrite-oxidized and 1 mol / L PBS buffer was prepared, wherein the heparin nitrite-oxidized in the PBS solution contained 1 wt %. The dendrimer-grafted PET film was immersed in 1 mL of the PBS solution and allowed to react at 25°C for 12 hours. After the reaction, the film was removed and ultrasonically cleaned in methanol for 10 minutes at a frequency of 80 kHz. The film was then dried under vacuum to obtain the medical PET film with both excellent blood compatibility and antibacterial properties provided by the present invention.

[0075] The PBS buffer is prepared using PBS buffer salt, and 1 mol / L PBS buffer is prepared according to the instructions for use of specific PBS buffer salt.

[0076] The medical PET film provided by the present invention with good blood compatibility and antibacterial ability is stored in a dry environment at 4°C.

[0077] In summary, the present invention provides a method for grafting and modifying the surface of a medical PET film with good blood compatibility and antibacterial ability. After the diazirine compound is grafted onto the surface of the PET film based on the carbene insertion principle, since the diazirine compound can provide functional groups such as bromine atoms that can further react, a substitution reaction can occur with the dendritic polymer with a large number of active amino groups on the outer layer, and the dendritic polymer with strong antibacterial ability is grafted onto the surface of the PET film, giving the PET film surface antibacterial ability. In addition, the outer amino group of the dendritic polymer can further react with other molecules to achieve refunctionalization of the PET film surface. A heparin derivative with an aldehyde group is obtained by nitrous acid oxidation of heparin, and the nitrous acid oxidized heparin is grafted onto the dendritic polymer by Schiff base reaction to achieve improvement of the blood compatibility and antibacterial ability of the medical PET film surface.

[0078] The third object of the present invention is to provide a modified PET material as described in the first object of the present invention or a modified PET material prepared by the method described in the second object of the present invention as a medical material.

[0079] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and a separate point value, and the separate point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0080] Compared with the prior art, the present invention has at least the following advantages:

[0081] The present invention provides a method for grafting modification on the surface of medical polymer materials such as PET. Carbene free radicals are generated by diazirine compounds under ultraviolet light. Side chains that can be used for modification are introduced on the surface of the PET film based on the C-H bond insertion principle of the carbene free radical, thereby achieving surface functional grafting modification of the PET film. The mechanical and optical properties of the medical polymer can be further improved, or the medical polymer can be given more functions.

[0082] The present invention provides a method for preparing a medical PET film with both excellent blood compatibility and antibacterial properties. Using the diazirine compound, polyamidoamine dendrimer, and nitrite-oxidized heparin described in the present invention as raw materials, the medical PET film with both excellent blood compatibility and antibacterial properties can be prepared. This solves the key issue of simultaneously improving the blood compatibility and antibacterial properties of the PET film surface, facilitating the manufacture of implantable medical devices that possess both antibacterial properties and are non-thrombogenic. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] Figure 1 This is an atomic force microscope (AFM) height image of the medical polyethylene terephthalate (PET) film with good blood compatibility and antibacterial ability prepared in Example 2 of the present invention;

[0084] Figure 2 This is a photograph of heparin oxidized by nitrite during the preparation of the medical PET film having good blood compatibility and antibacterial ability according to Example 2 of the present invention;

[0085] Figure 3 Photos of hemolysis tests of the dendrimer molecule-grafted PET film prepared in Example 2 of the present invention and the medical PET film with good blood compatibility and antibacterial ability prepared in Example 2 of the present invention;

[0086] Figure 4 Scanning electron microscope photographs of the platelet-rich plasma prepared in the test examples of the present invention coated on an untreated PET film, a diazirine compound-grafted PET film prepared in Example 2, a dendrimer molecule-grafted PET film, and a medical PET film with good blood compatibility and antibacterial properties prepared in Example 2 of the present invention, respectively;

[0087] Figure 5 Fluorescence confocal microscopy photographs of Staphylococcus aureus and Escherichia coli on an untreated PET film, a dendrimer-grafted PET film prepared in Example 2, and a medical PET film with good blood compatibility and antibacterial properties prepared in Example 2 of the present invention, respectively, in the test examples of the present invention;

[0088] Figure 6 This is a schematic diagram of the rat subcutaneous tissue test process in the test example of the present invention;

[0089] Figure 7 Photographs of H&E-stained epidermal tissue sections of rats 7 days after implantation of untreated PET film, the diazirine compound-grafted PET film prepared in Example 2, the dendrimer molecule-grafted PET film, and the medical PET film with good blood compatibility and antibacterial properties prepared in Example 2 of the present invention;

[0090] Figure 8 Schematic diagram of the preparation process of the modified PET material of the present invention;

[0091] Figure 9 This is an X-ray photoelectron spectroscopy (XPS) diagram of the modified PET material prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0092] The present invention will be described in detail below with reference to specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.

[0093] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any appropriate manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0094] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the scope of protection of the present invention.

[0095] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0096] Example 1

[0097] High-transmittance polyethylene terephthalate (PET) film (Dongguan Jinmei Electronic Materials) was cut into 1 cm × 1 cm sheets and cleaned in deionized water and methanol (Beijing Chemical Plant) using an ultrasonic cleaner (Shenzhen Guangming) for 10 minutes each, with an ultrasonic frequency of 80 kHz. After cleaning, it was dried in an oven at 37°C for 8 hours. 2 μL of 4-[3-(trifluoromethyl)-3H-bis(aziridin-3-yl)]benzyl bromide (Br-Dia, Japan TCI) was taken with a pipette and dropped on a 1 cm 2 After cleaning and drying, Br-Dia was evenly and completely applied to the center of the PET film surface using a PET brush. The coated PET film was placed in a UV light box (Qingdao Jason HeaChips) and reacted under 365nm UV light with an intensity of 0.5mW / cm 2 The film was taken out after the reaction, ultrasonically cleaned in methanol for 10 minutes at a cleaning frequency of 80 kHz, and dried under vacuum conditions to obtain a diazirine compound grafted PET film (Dia-g-PET).

[0098] Dia-g-PET was placed in a 12-well plate (NEST) and 1 mL of a 1wt% PAMAM methanol solution (Weihai Chenyuan) was added. The Dia-g-PET was immersed in the PAMAM solution and allowed to react in a closed environment at 25°C for 12 hours. After the reaction, the film was removed and ultrasonically cleaned in methanol for 10 minutes at 80 kHz. The film was then dried under vacuum to obtain a dendrimer-grafted PET film (PAMAM-g-PET).

[0099] Weigh 0.625g of heparin sodium (185 USP units / mg, Macklin) and dissolve it in deionized water to prepare 25mL of solution. Transfer the heparin sodium solution to a 250mL beaker. Nitrous acid is prepared using dilute sulfuric acid and sodium nitrite solution, wherein the dilute sulfuric acid concentration is 0.5mol / L and the sodium nitrite solution concentration is 5.5mol / L. Dilute sulfuric acid is prepared using 95% concentrated sulfuric acid (Beijing Chemical Plant) diluted with deionized water and transferred to a suitable container after preparation. Sodium nitrite (Beijing Chemical Plant) is prepared using deionized water. Nitrous acid is prepared in a fume hood by measuring 28.5mL of dilute sulfuric acid and 71.4mL of sodium nitrite solution respectively. Pour the dilute sulfuric acid and sodium nitrite solution into a 150mL beaker in turn, stir and mix in the fume hood to obtain fresh nitrous acid, and pour it into the beaker containing the heparin sodium solution. The reaction lasted for 10 minutes. After the reaction, the system was neutralized with 1 mol / L sodium hydroxide solution to a pH of 8.6, and the pH value of the solution was measured using a pH meter. The neutralized product was dialyzed with deionized water using an 8000Da dialysis bag, and the deionized water was replaced at least every 3 hours for a total of 4 times. The dialyzed product was placed in a refrigerator and frozen at -80°C for 12 hours. It was freeze-dried using a freeze dryer (Beijing Boyikang) to obtain a white cotton-like nitrite-oxidized heparin sample, which was sealed and refrigerated in a refrigerator at 4°C. Gel permeation chromatography (GPC) analysis showed that the molecular weight of the obtained nitrite-oxidized heparin was 17±5.1kDa.

[0100] A solution of nitrite-oxidized heparin and 1 mol / L PBS buffer was prepared, wherein the nitrite-oxidized heparin was 1 wt%. The PBS buffer was prepared from PBS buffer salt (BioSharp). A packet of PBS buffer salt was poured into a 2 L volumetric flask, and 2 L of buffer was prepared with deionized water. The flask was sealed and stored at 25°C. PAMAM-g-PET was immersed in 1 mL of nitrite-oxidized heparin PBS solution in a 12-well plate and allowed to react at 25°C for 12 hours. After the reaction, the film was taken out, ultrasonically cleaned in methanol for 10 minutes at a cleaning frequency of 80 kHz, and dried under vacuum conditions. After AFM and XPS characterization, a medical PET film (Hep1-g-PET) with good blood compatibility and antibacterial ability was obtained, which can be used to make implantable devices. An 80 nm raised area was observed on the surface of the film under AFM. Hep1-g-PET was placed in a culture dish and sealed, and stored in a refrigerator at 4°C; the schematic diagram of the preparation process of the above-mentioned modified PET material of the present invention is shown as follows. Figure 8 shown.

[0101] Example 2

[0102] High-transmittance polyethylene terephthalate (PET) film (Dongguan Jinmei Electronic Materials) was cut into 1 cm × 1 cm sheets and cleaned in deionized water and methanol (Beijing Chemical Plant) using an ultrasonic cleaner (Shenzhen Guangming) for 10 minutes each, with an ultrasonic frequency of 80 kHz. After cleaning, it was dried in an oven at 37 ° C for 8 hours. 2 μL of 4-[3-(trifluoromethyl)-3H-bis(aziridin-3-yl)]benzyl bromide (Br-Dia, TCI) was taken with a pipette and dropped on a 1 cm 2 After cleaning and drying, Br-Dia was evenly and completely applied to the center of the PET film surface using a PET brush. The coated PET film was placed in a UV light box (Qingdao Jason HeaChips) and reacted under 365nm UV light with an intensity of 0.5mW / cm 2 The film was taken out after the reaction, ultrasonically cleaned in methanol for 10 minutes at a cleaning frequency of 80 kHz, and dried under vacuum conditions to obtain a diazirine compound grafted PET film (Dia-g-PET).

[0103] Dia-g-PET was placed in a 12-well plate (NEST) and 1 mL of a 1wt% PAMAM methanol solution (Weihai Chenyuan) was added. The Dia-g-PET was immersed in the PAMAM solution and allowed to react in a closed environment at 25°C for 12 hours. After the reaction, the film was removed and ultrasonically cleaned in methanol for 10 minutes at 80 kHz. The film was then dried under vacuum to obtain a dendrimer-grafted PET film (PAMAM-g-PET).

[0104] Weigh 0.625g of heparin sodium (185 USP units / mg, Macklin) and dissolve it in deionized water to prepare 25mL of solution. Transfer the heparin sodium solution to a 250mL beaker. Nitrous acid is prepared using dilute sulfuric acid and sodium nitrite solution, wherein the dilute sulfuric acid concentration is 0.5mol / L and the sodium nitrite solution concentration is 5.5mol / L. Dilute sulfuric acid is prepared using 95% concentrated sulfuric acid (Beijing Chemical Plant) diluted with deionized water and transferred to a suitable container after preparation. Sodium nitrite (Beijing Chemical Plant) is prepared using deionized water. Nitrous acid is prepared in a fume hood by measuring 28.5mL of dilute sulfuric acid and 71.5mL of sodium nitrite solution respectively. Pour the dilute sulfuric acid and sodium nitrite solution into a 150mL beaker in turn, stir and mix in the fume hood to obtain fresh nitrous acid, and pour it into the beaker containing the heparin sodium solution. The reaction lasted for 20 minutes. After the reaction, the system was neutralized to pH 8.5 with 1 mol / L sodium hydroxide solution, and the pH value of the solution was measured using a pH meter. The neutralized product was dialyzed with deionized water using an 8000Da dialysis bag, and the deionized water was replaced at least every 3 hours, for a total of 4 times. The dialyzed product was placed in a refrigerator and frozen at -80°C for 12 hours. It was freeze-dried using a freeze dryer (Beijing Boyikang) to obtain a white cotton-like nitrite-oxidized heparin sample, which was sealed and refrigerated in a refrigerator at 4°C. GPC analysis showed that the molecular weight of the obtained nitrite-oxidized heparin was 11±4.4kDa, and the photo of the obtained oxidized heparin is as shown below. Figure 2 shown.

[0105] A solution of nitrite-oxidized heparin and 1 mol / L PBS buffer was prepared, wherein the nitrite-oxidized heparin was 1 wt%. The PBS buffer was prepared from PBS buffer salt (BioSharp). A packet of PBS buffer salt was poured into a 2 L volumetric flask, and 2 L of buffer was prepared with deionized water. The flask was sealed and stored at 25°C. PAMAM-g-PET was immersed in 1 mL of nitrite-oxidized heparin PBS solution in a 12-well plate and allowed to react at 25°C for 12 hours. After the reaction, the film was taken out, ultrasonically cleaned in methanol for 10 minutes at a cleaning frequency of 80 kHz, and dried under vacuum conditions. After AFM and XPS characterization, a medical PET film (Hep2-g-PET) with good blood compatibility and antibacterial ability was obtained, and its atomic force microscope (AFM) height map is shown as follows. Figure 1 As shown in Figure 2, a 68 nm raised area was observed on the film surface under AFM. The Hep-g-PET was placed in a culture dish, sealed, and stored in a refrigerator at 4°C.

[0106] Example 3

[0107] High-transmittance polyethylene terephthalate (PET) film (Dongguan Jinmei Electronic Materials) was cut into 1 cm × 1 cm sheets and cleaned in deionized water and methanol (Beijing Chemical Plant) using an ultrasonic cleaner (Shenzhen Guangming) for 10 minutes each, with an ultrasonic frequency of 80 kHz. After cleaning, it was dried in an oven at 37°C for 8 hours. 2 μL of 4-[3-(trifluoromethyl)-3H-diaziridin-3-yl]benzyl bromide (Br-Dia, TCI) was taken with a pipette and dropped on a 1 cm 2 After cleaning and drying, Br-Dia was evenly and completely applied to the center of the PET film surface using a PET brush. The coated PET film was placed in a UV light box (Qingdao Jason HeaChips) and reacted under 365nm UV light with an intensity of 0.5mW / cm 2 The film was taken out after the reaction, ultrasonically cleaned in methanol for 10 minutes at a cleaning frequency of 80 kHz, and dried under vacuum conditions to obtain a diazirine compound grafted PET film (Dia-g-PET).

[0108] Dia-g-PET was placed in a 12-well plate (NEST) and 1 mL of a 1wt% PAMAM methanol solution (Weihai Chenyuan) was added. The Dia-g-PET was immersed in the PAMAM solution and allowed to react in a closed environment at 25°C for 12 hours. After the reaction, the film was removed and ultrasonically cleaned in methanol for 10 minutes at 80 kHz. The film was then dried under vacuum to obtain a dendrimer-grafted PET film (PAMAM-g-PET).

[0109] Weigh 0.625g of heparin sodium (185 USP units / mg, Macklin) and dissolve it in deionized water to prepare 25mL of solution. Transfer the heparin sodium solution to a 250mL beaker. Nitrous acid is prepared using dilute sulfuric acid and sodium nitrite solution, wherein the dilute sulfuric acid concentration is 0.5mol / L and the sodium nitrite solution concentration is 5.5mol / L. Dilute sulfuric acid is prepared using 95% concentrated sulfuric acid (Beijing Chemical Plant) diluted with deionized water and transferred to a suitable container after preparation. Sodium nitrite (Beijing Chemical Plant) is prepared using deionized water. Nitrous acid is prepared in a fume hood by measuring 28.5mL of dilute sulfuric acid and 71.5mL of sodium nitrite solution respectively. Pour the dilute sulfuric acid and sodium nitrite solution into a 150mL beaker in turn, stir and mix in the fume hood to obtain fresh nitrous acid, and pour it into the beaker containing the heparin sodium solution. The reaction lasted for 45 minutes. After the reaction, the pH of the system was neutralized to 8.6 with a 1 mol / L sodium hydroxide solution, and the pH value of the solution was measured using a pH meter. The neutralized product was dialyzed with deionized water, using an 8000Da dialysis bag, and the deionized water was replaced at least every 3 hours for a total of 4 times. The dialyzed product was placed in a refrigerator, frozen at -80°C for 12 hours, and freeze-dried using a freeze dryer (Beijing Boyikang) to obtain a white cotton-like nitrite-oxidized heparin sample, which was sealed and refrigerated in a refrigerator at 4°C. GPC analysis showed that the molecular weight of the obtained nitrite-oxidized heparin was 7±2.1kDa.

[0110] A solution of nitrite-oxidized heparin was prepared with 1 mol / L PBS buffer, in which the nitrite-oxidized heparin was 1 wt%. The PBS buffer was prepared from PBS buffer salt (BioSharp). A packet of PBS buffer salt was poured into a 2 L volumetric flask, and 2 L of buffer was prepared with deionized water. The flask was sealed and stored at 25 ° C. PAMAM-g-PET was immersed in 1 mL of nitrite-oxidized heparin PBS solution in a 12-well plate and allowed to react at 25 ° C for 12 hours. After the reaction, the film was removed, ultrasonically cleaned in methanol for 10 minutes at a cleaning frequency of 80 kHz, and dried under vacuum conditions. After AFM and XPS characterization, a medical PET film (Hep3-g-PET) with good blood compatibility and antibacterial ability was obtained, which can be used to make implantable devices. A 41 nm raised area was observed on the surface of the film under AFM. Hep3-g-PET was placed in a culture dish and sealed and stored in a refrigerator at 4 ° C.

[0111] Example 4

[0112] The experimental process is basically the same as that of Example 1, with the only difference being that the amino-terminated polyamidoamine dendrimer used is the 7th generation polyamidoamine dendrimer.

[0113] Example 5

[0114] The experimental process is basically the same as that of Example 1, with the only difference being that the amino-terminated polyamidoamine dendrimer used is a disulfide core polyamidoamine dendrimer.

[0115] Test Case

[0116] The above-mentioned film was subjected to structural characterization, blood compatibility test, antibacterial performance test and biocompatibility test. The medical PET film with good blood compatibility and antibacterial ability described in the present invention can be confirmed to have grafted nitrite-oxidized heparin on the surface through X-ray photoelectron spectroscopy (XPS).

[0117] The blood compatibility of the medical PET film having both good blood compatibility and antibacterial ability of the present invention can be evaluated through a hemolysis test and a platelet surface adsorption test.

[0118] The antibacterial ability of the medical PET film having both good blood compatibility and antibacterial ability of the present invention can be evaluated by an in vitro bacterial live / dead staining test.

[0119] The biocompatibility of the medical PET film having good blood compatibility and antibacterial ability of the present invention can be evaluated by implanting the medical PET film of the present invention into rat epidermal tissue and staining epidermal tissue sections 7 days after implantation.

[0120] Structural characterization:

[0121] The surface structure of the grafted membrane was further confirmed by XPS, and the combined energy spectrum was as follows Figure 9 As shown. After the grafting of diazirine compounds (Br-Dia), f1, Br 3p, and Br 3d peaks appeared, indicating that the phenyl bromine structure was chemically modified on the PET surface through carbenzene. After the introduction of PAMAM (PAMAM-g-PET), the peak intensity of O 1s decreased significantly because the O / C ratio of PAMAM was lower than that of PET. At the same time, as the N / C ratio of PAMAM was higher than that of PET, the N1s peak intensity of PAMAM-g-PET increased. These results indicate that the grafting of PAMAM on PET was successful. After the introduction of oxidized heparin, the S2p peak appeared, and the O / C ratio increased significantly. These results indicate that the heparin chains were attached to the membrane surface through the reaction of aldehydes and primary amine groups. The S2p peak intensity of Hep3-g-PET was significantly higher than that of Hep1-g-PET and Hep2-g-PET, which reflects that the surface of Hep3-g-PET contains more heparin chains than the other two samples.

[0122] Blood compatibility test:

[0123] The Dia-g-PET film, PAMAM-g-PET film, Hep2-g-PET film and ultrasonically cleaned and dried PET film obtained in Example 2 were immersed in 10 mL of 0.9% mass-volume fraction normal saline and soaked at 37°C for 72 hours to obtain the leachate of each group of films. 50 mL of anticoagulated fresh rabbit blood (Beijing Borsi Technology) was diluted to 100 mL with normal saline. 0.2 mL of diluted rabbit blood was added dropwise to each group of film leachate and kept warm at 37°C for 1 hour. The mixed solution was taken out and centrifuged using a centrifuge (Beijing Baiyang) at a speed of 3000 r / min for 15 minutes. After centrifugation, the supernatant of each group of mixed solutions was taken out, and the absorption intensity of the clear solution under 545 nm visible light was recorded using an ultraviolet-visible light analyzer (Shimadzu) to obtain the hemolysis rate of each group of film leachate, as shown in Table 1 below. The pictures of the hemolysis test results of PAMAM-g-PET and Hep2-g-PET are shown in Figure 3 .

[0124] Table 1 Hemolysis rate of PET film before and after surface grafting modification

[0125] film PET Dia-g-PET PAMAM-g-PET Hep2-g-PET Hemolysis rate / % 1.1±0.17 1.6±0.18 7.2±0.24 1.2±0.18

[0126] Because the outer amino groups of the amino-terminated dendrimer PAMAM are positively charged, they can cause red blood cells to rupture, causing the red pigment in the red blood cells to diffuse throughout the centrifuge tube, resulting in hemolysis. The hemolysis rate is significantly higher than that of PET and Dia-g-PET before grafting modification. After the heparin derivative is grafted onto the surface, the outer amino groups of PAMAM are consumed, significantly reducing the hemolysis rate and improving blood compatibility.

[0127] Based on the principle that Acid Orange II can bind to the amino groups on the film surface at pH 3, the absorption intensity of the film at 485 nm was measured using a UV-visible light analyzer to determine the density of amino groups on the film surface. UV-visible light analysis showed that the amino group grafting density on the PAMAM-g-PET surface at 485 nm was 2.7 ± 0.11 × 10 -9 mol / cm 2 The amino grafting density on the surface of Hep-g-PET was 2.4±0.19×10 -9 mol / cm 2 , which verified the fact that the outer amino groups of PAMAM were consumed after heparin derivatives were grafted onto the surface.

[0128] Antithrombotic ability assay:

[0129] 100mL of anticoagulated fresh rabbit blood (Beijing Borsi Technology) was centrifuged at 37°C with a speed of 800r / min for 10 minutes using a centrifuge (Beijing Baiyang). After centrifugation, the supernatant was taken and centrifuged at 37°C with a speed of 2000r / min for 15 minutes. After centrifugation, the supernatant was removed to obtain platelet-rich plasma (PRP). The Dia-g-PET film, PAMAM-g-PET film, Hep2-g-PET film and ultrasonically cleaned and dried PET film obtained in Example 2 were immersed in 10mL of PBS buffer and soaked at 37°C for 2 hours. Each group of films was taken out, and 0.1mL of PRP was added to the film and soaked at 37°C for 2 hours. After soaking, the platelets not attached to the surface were washed with PBS buffer. Glutaraldehyde (50wt% aqueous solution, Aladdin) was diluted to 2.5wt% using PBS buffer. Each film group was immersed in a dilute glutaraldehyde solution and stored at 4°C for 12 hours to fix the platelets on the films. The films were then sequentially dehydrated by immersion in aqueous ethanol solutions of varying concentrations (10%, 25%, 50%, 75%, and 100%, by volume), each concentration maintained for 20 minutes. 100% ethanol was prepared from anhydrous sodium sulfate (Beijing Chemical Plant) using anhydrous ethanol (Beijing Chemical Plant). The platelet morphology on the film surface was observed using a scanning electron microscope (SEM, JEOL, JSM-6700M). The anti-thrombotic ability of each film group was determined by comparing the platelet adhesion density on the film surface.

[0130] Figure 4 The surface morphology of platelets on PET, Dia-g-PET, PAMAM-g-PET, and Hep-g-PET films was demonstrated. After grafting with diazirine compounds, platelet adhesion density on the films increased, reaching 189±28.8% higher than on PET films. After grafting with dendrimers, platelet aggregation density on the films increased to 267±21.9% higher than on PET films, indicating that platelets adhere more readily to Dia-g-PET and PAMAM-g-PET films, potentially leading to thrombosis. These results demonstrate that platelets have difficulty adhering to Hep2-g-PET films, with adhesion density only 29±12.1% of that on PET films. This significantly improves the antithrombotic properties of PET films, facilitating their application in the manufacture of implantable devices that combine antibacterial properties with non-thrombogenic properties.

[0131] Antibacterial ability determination:

[0132] Figure 5The results of in vitro live-death staining tests on Staphylococcus aureus (S.Aureus) and Escherichia coli (E.Coli) on the PET film of Example 2, PAMAM-g-PET film, and Hep2-g-PET film are presented to test the antibacterial ability of each film surface. After the bacteria were stained, killed bacteria appeared red under a confocal fluorescence microscope (CLSM), while live bacteria appeared green, thereby obtaining the survival rate of bacteria on the film surface. The concentration of Staphylococcus aureus and E.Coli was 1×10 8 4 mL of the dilution (CFU / mL) was dripped onto the surface of each film group and incubated at 37°C for 3 hours. The bacterial survival rates are shown in Table 2. Due to the large number of free amino groups on the outer layer of PAMAM, the survival rates of Staphylococcus aureus and Escherichia coli were significantly reduced after grafting with PAMAM, and the antibacterial ability of the PET film surface was significantly improved. After grafting with a heparin derivative (i.e., oxidized heparin), the survival rates of Staphylococcus aureus and Escherichia coli were improved compared to PAMAM-g-PET films due to the consumption of amino groups by nitrous oxide-oxidized heparin. However, the survival rate was still significantly lower than that of PET films, indicating that Hep2-g-PET films still have good antibacterial ability against Staphylococcus aureus and Escherichia coli.

[0133] Table 2 Bacterial survival rate of PET film before and after surface grafting modification

[0134] Staphylococcus aureus Escherichia coli PET >99% >99% PAMAM-g-PET 8±2.9% 4±2.6% Hep2-g-PET 20±4.1% 33±14.4%

[0135] Figure 6 A schematic diagram shows the animal testing process of implanting a film into the subcutaneous tissue of rats. The biocompatibility of each film group was compared based on the degree of subcutaneous tissue response to the film. Figure 7 Photographs of H&E-stained epidermal tissue sections from rats 7 days after implantation of the PET film from Example 2, Dia-g-PET film, PAMAM-g-PET film, and Hep2-g-PET film. Tissue reacts with the phenyl bromide groups on the Dia-g-PET film and the free amino groups on the surface of the PAMAM-g-PET film, damaging the epidermal tissue. However, grafting of the heparin derivative reduces the tissue reaction, significantly improving biocompatibility.

[0136] The remaining embodiments of the present invention also achieved the same trend as Example 2, that is, the PAMAM-g-PET film had very good antibacterial ability, but the modification effect of blood compatibility and biocompatibility was poor; the Hep-g-PET film had both good blood compatibility and antibacterial ability, and it not only had very good antibacterial ability, but also had significantly improved blood compatibility and biocompatibility compared to the unmodified PET material.

[0137] In summary, the present invention provides a surface grafting technology for medical PET films that combines excellent blood compatibility with antimicrobial properties. This technology addresses the critical issue of simultaneously improving the blood compatibility and antimicrobial properties of PET films without affecting the bulk properties of the film itself. First, by leveraging the ability of diaziridine compounds to generate carbene free radicals under ultraviolet light, bromine atoms are introduced onto the surface of the PET film using the principle of carbene C-H bond insertion. Then, amino-terminated dendrimers are grafted onto the surface via a substitution reaction, imparting antimicrobial properties to the film surface. Finally, an aldehyde-containing oxidized heparin derivative is grafted onto the film surface via a Schiff base reaction to improve the film's blood compatibility. The PET film produced by this invention not only kills more than 50% of Staphylococcus aureus and Escherichia coli, but also reduces the platelet adhesion density on the film surface to less than 80% of that of untreated PET film, resulting in a hemolysis rate of less than 2%. Rat epidermal tissue exhibits no significant reaction to the film, demonstrating both excellent blood compatibility and antimicrobial properties. The film can be used in the manufacture of biological devices such as implantable devices.

[0138] The present invention has been described in detail above with reference to specific embodiments and exemplary examples. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will appreciate that various equivalent substitutions, modifications, or improvements may be made to the technical solutions and implementations of the present invention without departing from the spirit and scope of the present invention, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be determined by the appended claims.

[0139] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of conflict, the definitions in this specification shall prevail.

[0140] When this specification uses the prefix "well known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, the objects introduced by the prefix include those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become generally recognized in the art to be suitable for similar purposes.

[0141] In the context of this specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A modified PET material, characterized in that: The modified PET material is obtained by grafting a halogen-containing diaziridine compound and an amino-terminated polyamidoamine dendrimer with antibacterial ability on the surface of the PET material in sequence, and then grafting optionally with oxidized heparin.

2. The modified PET material according to claim 1, characterized in that: The halogen-containing diaziridine compound is a compound that can generate carbene radicals under ultraviolet light; preferably, the halogen-containing diaziridine compound is selected from 4-[3-(trifluoromethyl)-3H-diaziridine-3-yl]benzyl bromide.

3. The modified PET material according to claim 1, characterized in that: The amino-terminated polyamidoamine dendrimer is at least one of a fifth-generation ethylenediamine core polyamidoamine dendrimer, a disulfide core polyamidoamine dendrimer, or a seventh-generation polyamidoamine dendrimer.

4. The modified PET material according to claim 1, characterized in that: The oxidized heparin is a heparin derivative having an aldehyde group.

5. A method for preparing a modified PET material, characterized in that: The following steps are involved: Step (1) grafting the PET material with a halogen-containing diaziridine compound to obtain an intermediate Dia-g-PET; Step (2) grafting the intermediate Dia-g-PET with an amino-terminated polyamidoamine dendrimer having antibacterial ability to obtain a modified PET material PAMAM-g-PET; Optionally, step (3), grafting the PAMAM-g-PET with oxidized heparin to obtain a modified PET material Hep-g-PET; The modified PET material according to any one of claims 1 to 3 is preferably prepared by the method described.

6. The method for preparing the modified PET material according to claim 5, characterized in that: Step (1), washing the PET material, drying it, and then subjecting it to a grafting reaction with a halogen-containing diaziridine compound under ultraviolet light; Preferably, The PET material is a PET film, and a halogen-containing diaziridine compound is uniformly coated on the surface of the PET film and then subjected to a grafting reaction under ultraviolet light; The ratio of the PET material to the halogen-containing diaziridine compound is 1 cm 2 : 1.5~2.5μL; preferably 1cm 2 :2.0~2.5μL; During the grafting reaction, the wavelength of the ultraviolet light is 355 to 380 nm, preferably 365 to 370 nm; The intensity of ultraviolet light is 0.4~0.6mW / cm 2 ; preferably 0.4 to 0.5 mW / cm 2 ; The irradiation time of ultraviolet light is 4 to 6 minutes, preferably 5 to 6 minutes.

7. The method for preparing the modified PET material according to claim 5, characterized in that: Step (2), immersing the intermediate Dia-g-PET in a solution containing the amino-terminated polyamidoamine dendrimer having antibacterial ability to carry out a grafting reaction, Preferably, The concentration of the solution of the amino-terminated polyamidoamine dendritic polymer having antibacterial ability is 0.8 to 1.1 wt %; preferably 0.9 to 1.0 wt %; and / or, The grafting reaction is carried out in a closed environment. Further preferably, the grafting reaction temperature is 20 to 30° C.; preferably 23 to 25° C.; and / or, The grafting reaction time is 8 to 12 hours, preferably 10 to 12 hours.

8. The method for preparing the modified PET material according to claim 5, characterized in that: Step (3), washing the PAMAM-g-PET, drying it, and immersing it in a solution containing oxidized heparin to carry out a grafting reaction, thereby obtaining a modified PET material Hep-g-PET; Preferably, The solution containing oxidized heparin is a solution prepared by oxidized heparin and PBS buffer; and / or, The temperature of the grafting reaction is 20 to 30° C.; preferably 23 to 25° C.; and / or, The grafting reaction time is 8 to 16 hours, preferably 12 to 16 hours; Further preferably, the concentration of oxidized heparin in the solution containing oxidized heparin is 0.8 to 1.1 wt %; preferably 1.0 to 1.1 wt %; and / or, The molar concentration of PBS in the solution containing oxidized heparin is 1.0-1.2 mol / L.

9. The method for preparing the modified PET material according to claim 5, characterized in that: Step (3), The oxidized heparin is a heparin derivative having an aldehyde group obtained by oxidation with nitrous acid; Preferably, the nitrous acid solution is reacted with the heparin sodium solution, and then alkali is added for neutralization, and then dialyzed and freeze-dried to obtain oxidized heparin; More preferably, The concentration of the nitrous acid solution is 5.4-5.6 mol / L; and / or, The concentration of the heparin sodium solution is 0.020-0.025 g / mL; and / or, The volume ratio of the nitrous acid solution to the heparin sodium solution is 100:20-30; and / or, The reaction time is 10 to 45 minutes; and / or, The reaction temperature is 23-25°C; and / or, The alkali used for the alkali neutralization is a sodium hydroxide aqueous solution, and the pH value is neutralized to 8.2-8.

8.

10. Use of the modified PET material according to any one of claims 1 to 4 or the modified PET material prepared by the method according to any one of claims 5 to 9 as a medical material.

Citation Information

Patent Citations

  • Method for ultraviolet light induced surface amination of polymer

    CN113388144A

  • Heparinized PVC (polyvinyl chloride) material, preparation method thereof and application of heparinized PVC material as medical instrument

    CN114106493A

  • Biocompatible sterilizing and anti-sticking PET (Polyethylene Terephthalate) material as well as preparation method and application thereof

    CN115975242A

  • Heparin anticoagulant coating as well as preparation method and application thereof

    CN117482303A

  • Animal-derived biological material with synergistic anticoagulation and anti-calcification functions and preparation method thereof

    CN118271629A